2008
DOI: 10.1016/j.alcohol.2008.03.131
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, intestinal bacterial growth, intestinal permeability to endotoxin, and medical consequences: Summary of a symposium

Abstract: This report is a summary of the symposium on Alcohol, Intestinal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
223
1
21

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(250 citation statements)
references
References 93 publications
5
223
1
21
Order By: Relevance
“…In addition, alcohol metabolism by Gram-negative bacteria and intestinal epithelial cells can result in accumulation of acetaldehyde, which in turn can increase intestinal permeability by opening intestinal tight junctions. Increased intestinal permeability can lead to increased transfer of LPS from the intestine to portal and systemic circulation [28]. Furthermore, chronic alcohol consumption upregulates hepatic TLR4 and sensitizes it to LPS to enhance TNF-a production [29].…”
Section: Alcoholic Liver Diseasementioning
confidence: 99%
“…In addition, alcohol metabolism by Gram-negative bacteria and intestinal epithelial cells can result in accumulation of acetaldehyde, which in turn can increase intestinal permeability by opening intestinal tight junctions. Increased intestinal permeability can lead to increased transfer of LPS from the intestine to portal and systemic circulation [28]. Furthermore, chronic alcohol consumption upregulates hepatic TLR4 and sensitizes it to LPS to enhance TNF-a production [29].…”
Section: Alcoholic Liver Diseasementioning
confidence: 99%
“…Evidence indicates that alcohol consumption causes enteric dysbiosis and bacterial overgrowth [139,140] that leads to a significant increase in gut permeability and consequently high levels of LPS in the portal circulation [141][142][143] . Acetaldehyde contributes to alter intestinal barrier function and to promote endotoxin translocation by disrupting tight and adherens junctions in human colonic mucosa [144] via increasing tyrosine phosphorylation of occludin and E-cadherin.…”
Section: Ethanol Oxidation and Activation Of Innate And Adaptive Immumentioning
confidence: 99%
“…This study showed that Gln supplementation significantly increased LBP, which was in accordance with the study of Jafari et al (2006) where dairy cows were infused with 106 g/d and 212 g/d Gln. LBP can promote LPS to transfer to CD-14 to activate mononuclear macrophages and endothelial cells, which in turn activates Kupffer cells in liver to clear LPS via Toll-like receptors-4 (Purohit et al 2008). Furthermore, LBP can transfer LPS to serum lipoproteins, such as low-density lipoprotein (LDL) and highdensity lipoprotein (HDL), for clearing LPS from the bloodstream (Jafari et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…(2) Gln can prevent the reduction of transepithelial electrical resistance of intestinal epithelial cells caused by LPS, reduce the redistribution of occludin, zona occludens-1 (ZO-1), E-cadherin, and b-catenin from the intercellular junctions to the intracellular compartments, and decrease the acetaldehyde-induced dissociation of occludin, ZO-1, E-cadherin, and b-catenin from the actin cytoskeleton (Purohit et al 2008). (3) Gln can down-regulate the expression of intercellular adhesion molecule 1 in intestinal mucosa, thereby reduce its interaction with integrins including cluster of differentiation (CD)-11 and CD-18, so as to alleviate the activation and adhesion of neutrophils to intestinal endothelial cells, which helps to protect the intestinal mucosa (Gu et al 2006).…”
Section: Discussionmentioning
confidence: 99%